Evolution problems of Leray–Lions type with nonhomogeneous Neumann boundary conditions in metric random walk spaces. (August 2020) - Mazón, José M.; Solera, Marcos; Toledo, Julián
Abstract: In this paper we study evolution problems of Leray–Lions type with nonhomogeneous Neumann boundary conditions in the framework of metric random walk spaces. This covers cases with the p -Laplacian operator in weighted discrete graphs and nonlocal operators with nonsingular kernel in R N .